How does burnout relate to daily work-related rumination and well-being of psychotherapists? A daily diary study among psychotherapeutic practitioners - Gossmann, Katharina; Schmid, Regina Franziska; Loos, Carina; Orthmann, Alessandra Barbara Anneliese; Rosner, Rita; Barke, Antonia (Frontiers in Psychiatry, 2023)
Objective: This is the first study to use a daily diary design to investigate the relationship between daily work-related rumination (WRR), daily well-being, and burnout symptoms among psychotherapeutic practitioners. Method: In total, N = 58 psychotherapeutic practitioners participated in the study. For four weeks, the participants received a daily evening prompt on weekdays asking about their WRR and well-being. The burnout level of the psychotherapists was assessed using Maslach Burnout Inventory (MBI) prior to the daily diary period and afterwards. The MBI measures the level of work-related distress on three subscales: emotional exhaustion (EE), depersonal-ization (DP), and personal achievement (PA). Two main analyses were performed: Based on the hierarchical structure of the data we performed random intercept and slopes models. These models examined the association between daily WRR and daily well-being, and the relationship between pre-burnout and daily WRR and daily mood. Secondly, linear regres-sions with the post-MBI subscales as criterion and the daily diary variables as predictors were calculated to assess their contribution to post-burnout. Results: The compliance rate in our study was 76.8%. Daily WRR and pre-assessment EE were associated with all aspects of reduced daily well-being: bad mood, increased nervous-ness, and tiredness after work. Daily tiredness and nervousness played a differential role in predicting post-burnout. Conclusion: Our results indicated that daily rumination and pre-EE were associated with reduced daily well-being. As we are the first to present a daily diary study among psycho-therapists, we examined the feasibility of the daily diary design in particular and ecological momentary assessment (EMA) in general in this population. Compliance rates compared well with other EMA studies, indicating that EMAs were a feasible assessment option for psychotherapeutic practitioners.